2007 IEEE Instrumentation &Amp; Measurement Technology Conference IMTC 2007 2007
DOI: 10.1109/imtc.2007.379013
|View full text |Cite
|
Sign up to set email alerts
|

Quadrature Bridge for R-C Comparisons based on Polyphase Digital Synthesis

Abstract: A coaxial quadrature bridge based on digital synthesis has been developed. The bridge compares two resistance standards (having nominal resistance R), with two capacitance standards (nominal capacitance C), at an angular frequency w (such that wRC 1).All standards are defined as two terminal-pair impedances. All voltages and currents employed in the bridge are generated by a multiphase direct digital synthesizer, constructed around a personal computer DAC board and a set of integrated amplifiers; the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The electromagnetic CC and the polyphase synthesized generator employed in the implementation are described in detail in [20] and [21]. The detector employed is a commercial Stanford Research mod.…”
Section: B Bridgementioning
confidence: 99%
“…The electromagnetic CC and the polyphase synthesized generator employed in the implementation are described in detail in [20] and [21]. The detector employed is a commercial Stanford Research mod.…”
Section: B Bridgementioning
confidence: 99%
“…4. The bridge measure the product C 1 C 2 in terms of R 1 R 2 ; it is an evolution of a similar bridge presented in [36].…”
Section: Quadrature Bridgementioning
confidence: 99%
“…Recently, we have shown that the concept of digitallyassisted bridges permit to achieve measurement uncertainties at the 10 −8 level, with the potential for further improvements [2], [3].…”
Section: Introductionmentioning
confidence: 99%